Correction of intestinal microbiocenosis as a preventive measure for progression of chronic kidney disease - M. S. Barilko; P. V. Seliverstov; V. G. Radchenko; A. A. Murzina (Медицинский совет, 2018)
At present, much attention is paid to the study of the influence of gut microbiota on the development of many diseases of internal organs, including chronic kidney disease. Thus, changes of gut microbiota in the qualitative and quantitative composition toward increasing the proteolytic flora, which is the source of the formation of uremic toxins, endotoxinemia, systemic inflammation, secondary immunodeficiency and cardiovascular complications, contribute to the worsening of the course and the progression of chronic kidney disease. That why the use of medicines which normalize gut microbiota, is the significant aspect of preventing the progression of chronic kidney disease.